An Empirical Study To Evaluate Capital Structure Determinants in Context of Indian Firms and To Compare These Determinants with UK Firms - Agarwal, Nirbharant (2013)
This study tries to find capital structure explanatory variables, for one of the most untouched developed economies (India) in capital structure literature and compare it with the results found in UK context. Therefore the primary aim of the study is to find capital structure determinants of Indian firms. Whereas the secondary aim of the study is to compare those results with the ones found in UK firms in hope to understand if country specific factors influence capital structure decisions. The data utilized in the regression model was collected from DataStream. The data consists of 222 UK companies listed on the London Stock Exchange and another 222 companies listed on the Indian National Stock Exchange over a period of ten year i.e. from 2003-2012. This study considers three(3) dependent variables, namely Long term Leverage (LTLEV), Total Leverage (TLEV) and Short term Leverage (STLEV), where LTLEV is considered to the main dependent variable and the rest two are merely used for comparison reasons. Whereas for the independent variable, the model in the study uses eight(8) variables which are Profitability (PROF), Size (SIZE), Growth (GRWTH), Tangibility (TANG), Non-Debt Tax Shield (NDTS), Liquidity (LIQD), Uniqueness (UNIQ), GDP growth rate (GDP).